In Chagas disease, transforming growth factor beta neutralization reduces Trypanosoma cruzi infection and improves cardiac performance - Ferreira, Roberto Rodrigues; de Souza, Elen Mello; Vilar-Pereira, Glaucia; Degrave, Wim M. S.; Abreu, Rayane da Silva; Meuser-Batista, Marcelo; Ferreira, Nilma Valéria Caldeira; Ledbeter, Steve; Barker, Robert H.; Bailly, Sabine; Feige, Jean-Jacques; Lannes-Vieira, Joseli; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic Chagasic cardiomyopathy (CCC), a progressive inflammatory and fibrosing disease, is the most prominent clinical form of Chagas disease, a neglected tropical disease caused by Trypanosoma cruzi infection. During CCC, the parasite remains inside the cardiac cells, leading to tissue damage, involving extensive inflammatory response and irregular fibrosis. Among the fibrogenic factors is transforming growth factor-β (TGF-β), a key cytokine controlling extracellular matrix synthesis and degradation. TGF-β is involved in CCC onset and progression, with increased serum levels and activation of its signaling pathways in the cardiac tissue, which crucially contributes to fibrosis. Inhibition of the TGF-β signaling pathway attenuates T. cruzi infection and prevents cardiac damage in an experimental model of acute Chagas disease. The aim of this study was to investigate the effect of TGF-β neutralization on T. cruzi infection in both in vitro and in vivo pre-clinical models, using the 1D11 monoclonal antibody. To this end, primary cultures of cardiac cells were infected with T. cruzi trypomastigote forms and treated with 1D11. For in vivo studies, 1D11 was administered in different schemes for acute and chronic phase models (Swiss mice infected with 104 parasites from the Y strain and C57BL/6 mice infected with 102 parasites from the Colombian strain, respectively). Here we show that the addition of 1D11 to cardiac cells greatly reduces cardiomyocyte invasion by T. cruzi and the number of parasites per infected cell. In both acute and chronic experimental models, T. cruzi infection altered the electrical conduction, decreasing the heart rate, increasing the PR interval and the P wave duration. The treatment with 1D11 reduced cardiac fibrosis and reversed electrical abnormalities improving cardiac performance. Taken together, these data further support the major role of the TGF-β signaling pathways in T. cruzi-infection and their biological consequences on parasite/host interactions. The therapeutic effects of the 1D11 antibody are promising and suggest a new possibility to treat cardiac fibrosis in the chronic phase of Chagas’ heart disease by TGF-β neutralization.